Re(claiming) Indigenous Identity Within Canada's Prison System: Indigenous Identity and Indigenous-Specific Prison Programming - Wellman, Stephanie (Université d'Ottawa / University of Ottawa, 2017)
The purpose of this thesis is to explore how Indigenous men understand Indigenous identity, how they experience Indigenous-specific programming while in prison, and how these experiences intersect. Through a number of qualitative semi-structured interviews, Indigenous men described their experiences of participating in Indigenous-specific programming while incarcerated; the data is then understood within an historical context of colonialism and assimilation policy. The key findings of these interviews highlight the importance and necessity of Indigenous-specific prison programming to incarcerated Indigenous men, as well as the healing potential of Indigenous culture and spirituality. However, systemic barriers in provincial prison systems prevent Indigenous men from being able to access such programming. This thesis also finds that Canada’s history of colonialism has affected the Indigenous identities of many of the research participants. Some spoke about culture and language loss as a direct result of colonization (the residential school system, the sixties-scoop, and the child welfare system) while others spoke about the indirect outcomes of colonization, such as marginalization and fragmented identities. Based on these findings the main conclusion is that while Canada is attempting to appear post-colonial in light of talks of renewed relationships and reconciliation, colonization of Indigenous men continues within the Canadian prison system. As incarcerated Indigenous men are denied access to culture and spirituality the prison itself is serving to further disconnect Indigenous people from being Indigenous and fostering the erasure of Indigenous identity from the Canadian settler state as a means of continuing what can be termed as the ‘civilizing’ project.